ISOLASI DAN IDENTIFIKASI BAKTERI PEREDUKSI SULFAT DARI KAWASAN PLTP KAMOJANG JAWA BARAT - Dwi Suhartanti (Universitas Muhammadiyah Semarang, 2004)
Tlte isolation and identification of sulfat reducing bacteria (SRB) had been performed at Kamojang Geothermal Power Plant. Isolation and identification of sulfat reducer bcrcteria from the soil and corroded steel bolt obtained from the area of Kamojang Geothermal power plant. Four (4) spesies of bacterias were obtained from the soil among them were Desulfotomaculum spl, Desulfutomaculum sp2, Desulfotomaculum sp3, Desulfomonas pigra, and ones (l) spesies from coruoded steel bolt Desulfovibrio sp.